STRATEGI PEMBELAJARAN BERBASIS PROYEK UNTUK MENUMBUHKAN KREATIVITAS SISWA - Rania Purba; Wahyuningtyas; Fiqi Nurmanda Sari (Jurnal Ilmiah Bina Edukasi, 2025)
This study was conducted because of the importance of creativity as a key skill in 21st century learning. The hypothesis proposed is that project-based learning strategies can foster students' creativity effectively. The research method uses a qualitative approach with data collection through observation, interviews, and documentation during the learning process. The results of the study revealed that the application of project-based learning strategies that prioritize collaboration between students, exploration of innovative ideas, and active reflection on the learning process and products. These findings confirm that project-based learning is an effective and relevant approach to be developed in the world of education to prepare students to face future challenges